2004
DOI: 10.1073/pnas.0402391101
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate mimicry between human ganglioside GM1 and Campylobacter jejuni lipooligosaccharide causes Guillain–Barré syndrome

Abstract: Molecular mimicry between microbial and self-components is postulated as the mechanism that accounts for the antigen and tissue specificity of immune responses in postinfectious autoimmune diseases. Little direct evidence exists, and research in this area has focused principally on T cell-mediated, antipeptide responses, rather than on humoral responses to carbohydrate structures. Guillain-Barré syndrome, the most frequent cause of acute neuromuscular paralysis, occurs 1-2 wk after various infections, in parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
357
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 461 publications
(363 citation statements)
references
References 31 publications
3
357
0
3
Order By: Relevance
“…The process is caused by paralysis of peripheral motor nerves by anti-ganglioside antibodies directed to lipopolysaccharide of Campylobacter jejuni. The major antibodies were identified as directed to GM1 (23). Antibodies causing more serious motor nerve paralysis were found to be directed to heterodimer structures, such as GD1a/GM1, GD1b/ GT1b, and GM1/GT1b, rather than single ganglioside structures (10,24).…”
Section: Discussionmentioning
confidence: 98%
“…The process is caused by paralysis of peripheral motor nerves by anti-ganglioside antibodies directed to lipopolysaccharide of Campylobacter jejuni. The major antibodies were identified as directed to GM1 (23). Antibodies causing more serious motor nerve paralysis were found to be directed to heterodimer structures, such as GD1a/GM1, GD1b/ GT1b, and GM1/GT1b, rather than single ganglioside structures (10,24).…”
Section: Discussionmentioning
confidence: 98%
“…This raises the possibility that antiganglioside antibodies and subsequent neuropathies result from cross-reactivity to C. jejuni LPSs via molecular mimicry (48,96,104). Initially, Yuki et al (96,98) reported that the LPS of C. jejuni isolated from a patient with GBS had a GM1-like structure, suggesting that the GM1 epitope-bearing LPS may function in the production of anti-GM1 antibodies in this patient.…”
Section: Oligosaccharides Of Lpss That Mimic Ganglioside Structuresmentioning
confidence: 99%
“…Several reports referred to the antigenic similarity between the components of Campylobacter spp. and peripheral myelin, causing immune-mediated demyelination [12,21,22].…”
mentioning
confidence: 99%